Pengaruh Green Accounting, Struktur Modal Dan Sales Growth Terhadap Financial Performance - Prawira, Anggun Wida (CV. ULIL ALBAB CORP, 2025)
This research aims to analyze the influence of Green Accounting, Capital Structure, and Sales Growth on Financial Performance measured by Return on Assets (ROA) in energy sector companies, particularly in the oil, gas, and coal subsector listed on the Indonesia Stock Exchange for the period 2021–2024. The research method used is quantitative with secondary data in the form of annual reports and sustainability reports of the companies. The sample was selected using purposive sampling technique with specific criteria, resulting in 10 companies as the research subjects. Data analysis was conducted using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results of the study indicate that Green Accounting has a significant positive effect on ROA, Sales Growth has a significant positive effect, while Capital Structure does not have a significant effect on ROA. This research provides practical implications for company management to strengthen sustainability strategies and capital efficiency in order to improve financial performance. In addition, this research can serve as an academic reference for the development of studies related to green accounting and financial performance in the energy sector, particularly in the oil, gas, and coal subsector.